Trace elements contents in Belarusian reservoirs and rivers bottom sediments according to monitoring - Vlasov, Boris P.; Zhukovskaya, Natallia V.; Kavalchyk, Nadzeya V. (Journal of the Belarusian State University. Geography and Geology, 2017)
The trace elements (Ti, V, Cr, Mn, Ni, Cu, Zn, Mo, Pb) accumulation in modern bottom sediments of Belarusian reservoirs and rivers in the places of higher aquatic vegetation growing has been analyzed on monitoring data for the period of 2000 –2015 years. The distribution of the studied elements majority (Ti, V, Cr, Mn, Ni, Cu, Pb) in the reservoir bottom sediments obeys lognormal law distribution. The lakes with the anomalous concentrations of Ni, V, Cu, Cr, Pb in the bottom sediments have been identified. The spatial distribution of Ti, Cr, Mn, Cu in the reservoirs bottom sediments is random. For Pb a cluster of high values in the North of Belarus (Osveiskoe, Bredno, Beloe and Mokhovoe lakes) has been revealed. The mean concentrations of V, Cr, Mn, Ni in the rivers bottom sediments are higher than in the reservoirs bottom sediments. The elements associations in the bottom sediments of reservoir and rivers have been identified by using principal component analysis. The elements of the first association (V, Cr, Ni, Cu, Pb) are concentrated mainly in the fine fractions. Ti is a slightly mobile element in most geochemical situations and forms a separate group as well in rivers bottom sediments as in lakes bottom sediments. Mn makes up the separate association that can be explained by manganese forms in the lakes sediments.